Developing paper-based devices for mapping agricultural pesticides and environmental contaminants - Menger, Ruth F., author; Henry, Charles S., advisor; Borch, Thomas, advisor; Ravishankara, A. R., committee member; Neilson, James R., committee member; Trivedi, Pankaj, committee member (Colorado State University. Libraries, 2021)
The detection of environmental contaminants is important to ensure the health of both humans and the environment. Currently, detection is done by instrumentation like liquid or gas chromatography coupled with mass spectrometry. While sensitive and selective for multiple analytes, these instruments suffer from disadvantages like large size, high sample cost, and the need for a trained analyst to run the samples. As an alternative, microfluidic paper-based analytical devices (µPADs) are becoming more common as inexpensive, fast, easy to use devices to detect and quantify a variety of analytes. My research has been focused on developing µPADs for three different analytes: pesticides, PFAS, and heavy metals. In order to ensure proper crop protection and pest management, it is important to manage and optimize pesticide application. Currently, this is done by water-sensitive papers, which often inaccurately portray the presence of pesticide due to humidity and extraneous water droplets that are not pesticide. In Chapter 2, I have developed a method that uses filter paper to capture a fluorescent tracer dye that has been mixed with the pesticide and then sprayed over the crop. The filter papers are imaged with a lightbox and Raspberry Pi camera system and then analyzed to determine percent coverage. After optimization and validation of the method to WSP, the filter paper method was used to evaluate pesticide distribution in a citrus grove in Florida (Chapter 3). The data from these field studies was used to make recommendations for which application method is best for the different types of pesticides. Paper-based devices are inherently limited by the inability to control fluid properties like mixing. In order to incorporate mixing but also retain a small device that does not require external power to initial flow, a microfluidic device was fabricated out of two glass slides. A staggered herringbone pattern is laser ablated into the slides, and a channel is formed by double-sided adhesive (Chapter 4). Mixing was quantified using blue and yellow dyes. A reaction between horseradish peroxidase and hydrogen peroxide was used as a representative enzymatic reaction and also to determine enzyme kinetics. Since the microfluidic device is made of glass, it is also compatible with non-aqueous solvents. Paper-based devices do not work well with organic solvents because the hydrophobic wax on the paper is dissolved by the solvent. In Chapter 5, the dissertation returns to traditional µPADs for environmental contaminants. Per- and polyfluoroalkyl substances (PFAS) are class of compounds that are highly persistent, toxic, bioaccumulative, and ubiquitous. While multiple instrument-based methods exist for sensitive and selective detection in a variety of matrices, there is a huge need for a fast, inexpensive, and easy-to-use sensor for PFAS detection. This would enable widespread testing of drinking water supplies, ensuring human health. A µPAD was developed for the detection of perfluorooctane sulfonate (PFOS) where the ion-pairing of PFOS and methylene green forms a purple circle. The diameter of the purple circle can be measured by the naked eye with a ruler or with the help of a smartphone to correlate the diameter back to PFOS concentration. At a cost of cents per sample, this µPAD enables fast and inexpensive detection of PFOS to ensure safe drinking water. A common issue with environmental µPADs is the relatively high limits of detection compared to what is needed for regulatory purposes. It can be challenging to lower the limits of detection without incorporating an external pretreatment and/or preconcentration step. As µPADs are small and handle only a small volume of sample (<120 µL), there is the possibility of increasing the sample capacity of the device but without significantly increasing the device size or analysis time. By adding multiple layers of absorbent filter paper underneath radial device for heavy metal detection, the sample volume increased to 1 mL, decreasing the limit of detection for a radial copper detection card from 100 ppb to 5 ppb (Chapter 6). The research presented here achieves the goal of developing µPADs for environmental contaminants. They can be used in different ways to visualize the presence of the contaminant for monitoring and management purposes, ultimately ensuring human and environmental health.
Zip file contains supplementary videos, no sound.
Keywords: pesticide; sensor; heavy metal; µPAD; PFAS